2024
DOI: 10.1111/srt.13538
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometrics study on the status quo and hot topics of pathogenesis of psoriasis based on Web of Science

Yujie Yang,
Xuwei Zheng,
Haiying Lv
et al.

Abstract: BackgroundPsoriasis is an immune‐mediated chronic inflammatory skin disease. Great progress has been made in the pathogenesis of psoriasis in recent years, but there is no bibliometric study on the pathogenesis of psoriasis. The purpose of this study was to use bibliometrics method to analyze the research overview and hot spots of pathogenesis of psoriasis in recent 10 years, so as to further understand the development trend and frontier of this field.MethodsThe core literatures on the pathogenesis of psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Therefore, n-3 DPA has a certain anti-inflammatory effect, which may play a role by reducing the inflammatory response of psoriasis lesions. On the other hand, it has been reported that the disturbance of intestinal flora can destroy the intestinal mucosal barrier, increase intestinal mucosal permeability, and reduce the metabolism of probiotics and short chain fatty acids, thus aggravating the intestinal inflammatory response in patients with psoriasis ( 61 ). n-3 DPA and EPA play an important role in maintaining the integrity of intestinal barrier, increasing the diversity of intestinal microbiota, and regulating intestinal immunity ( 23 , 29 ), both may play an important role in the gut-cutaneous axis by maintaining the balance between the gut microbiota, repairing the intestinal barrier, and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, n-3 DPA has a certain anti-inflammatory effect, which may play a role by reducing the inflammatory response of psoriasis lesions. On the other hand, it has been reported that the disturbance of intestinal flora can destroy the intestinal mucosal barrier, increase intestinal mucosal permeability, and reduce the metabolism of probiotics and short chain fatty acids, thus aggravating the intestinal inflammatory response in patients with psoriasis ( 61 ). n-3 DPA and EPA play an important role in maintaining the integrity of intestinal barrier, increasing the diversity of intestinal microbiota, and regulating intestinal immunity ( 23 , 29 ), both may play an important role in the gut-cutaneous axis by maintaining the balance between the gut microbiota, repairing the intestinal barrier, and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…CiteSpace software is run in a Java‐based environment and was first created by Chen MeiChao, a professor from Drexel University, United States. 13 , 14 The primary purpose of Citespace is to provide researchers with a graphical representation of the relationships between different scientific papers, authors, and institutions. This can be extremely useful for reviewing key areas of research and identifying current collaborators and research institutions.…”
Section: Introductionmentioning
confidence: 99%
“…11 Bibliometrics is one of the essential quantitative index evaluation methods, mainly based on the quantity and quality of academic publications, and makes objective evaluations via the characteristics of content and structure. 12,13 With the development of computer technology, large professional databases, and various software, for example, CiteSpace, helped to realize the automation, intelligence, and visualization of bibliometrics and significantly improved the evaluation efficiency. CiteSpace software is run in a Java-based environment and was first created by Chen MeiChao, a professor from Drexel University, United States.…”
mentioning
confidence: 99%
“… 9 In recent years, the role of lncRNA in skin diseases has begun to be emphasized, as it can disrupt cellular functions and activities through dysregulated expression, thereby inducing immune inflammatory responses and playing a crucial role in the pathogenesis of psoriasis. 10 , 11 An increasing number of studies have shown that lncRNAs have the potential to become ideal disease biomarkers because they are abnormally expressed in many tumors and participate in various types of regulation. 12 A previous study reported that six autophagy‐associated lncRNAs were potential molecular biomarkers and treatment targets for uveal melanoma (UM).…”
Section: Introductionmentioning
confidence: 99%